Adjuvants for a New Generation of Vaccines - Anthony C Allison; Noelene E Byars (Canadian Journal of Infectious Diseases)
Subunit antigens of viruses and other infectious agents in their natural configuration can be produced by recombinant DNA technology. To elicit protective immunity such antigens have to be administered with adjuvants that elicit cell-mediated immunity, including genetically restricted cytotoxicity, and that produce high affinity antibodies of protective isotypes. Antibodies of such isotypes (immunoglobulin G2a [IgG2a] in the mouse and IgG 1 in humans) efficiently activate complement and effect antibody-dependent cell-mediated cytotoxicity. Naturally occurring adjuvants such as lipopolysaccharide and muramyl dipeptide (MOP) are pyrogenic and produce uveitis and arthritis in susceptible experimental animal and human recipients. Synthetic analogues of MOP and monophosphoryl lipid A (MPL) retain adjuvant activity with reduced side effects. Adjuvants increase the expression of class II major histocompatibility complex on antigen-presenting cells and cytokine production: interferon-gamma augments the production of IgG2a antibodies in the mouse. Dispersion of antigens in water-oil emulsions, immunestimulating complexes or liposomes also increases immunogenicity, at least partly by targeting antigens to antigen-presenting cells. Inclusion of MOP analogues or MPL in such systems constitutes adjuvant formulations, such as MOP-A. When used with a variety of recombinant and other subunit antigens, such adjuvants elicit protective immunity in experimental animals. This strategy improves vaccines already in use (eg, influenza and hepatitis B) and makes possible new vaccines (herpesviruses, simian and human immunodeficiency viruses, respiratory syncytial virus and acellular pertussis).